Postshock sensing performance in transvenous defibrillation lead systems: analysis of detection and redetection of ventricular fibrillation. - Callans DJ; Swarna US; Schwartzman D; Gottlieb CD; Marchlinski FE (Journal of Cardiovascular Electrophysiology, 1995)
Introduction: The sensing performance of transvenous lead systems may be adversely affected by the delivery of high-energy shocks. This may be due to the proximity of the sensing and energy-delivery electrodes on transvenous leads. Methods and Results: The time required for detection of ventricular fibrillation and redetection after a failed first shock was compared in 93 patients with five different lead system-pulse generator combinations: Cadence[TM]-Endotak[TM] 60 series, Ventak P[TM]-Endotak[TM] 60 series, Jewel[TM]-Transvene[TM], Cadence[TM] -TVL[TM], and Cadence[TM]-Transvene[TM]. A total of 418 successful and 204 failed first shocks were delivered during induced ventricular fibrillation. Redetection times (RED) were consistently shorter than detection times (DET) in the Jewel-Transvene (RED minus DET: -1.9 ± 0.8 sec, P < 0.0001), the Cadence-TVL (-1.6 ± 1.0 sec, P < 0.0001), and the Cadence-Transvene combinations (-2.0 ± 0.9 sec, P < 0.0004). Redetection times were not significantly different than detection times in the Cadence-Endotak combination (-0.9 ± 3.1 sec; P = 0.09). Redetection times were significantly longer than detection times in the Ventak-Endotak combination (1.2 ± 2.3 sec; P = 0.034). Prolonged individual redetection episodes (> 8.2 sec) were observed in the Cadence-Endotak (7 [10%] of 73 episodes) and the Ventak-Endotak (4 [10%] of 39 episodes), but not in the Jewel-Transvene, the Cadence-TVL, and the Cadence-Transvene combinations. Conclusions: Redetection of ventricular fibrillation may be delayed in some transvenous lead-pulse generator combinations. Successful redetection of ventricular fibrillation following a failed first shock should be demonstrated prior to hospital discharge of patients with implantable defibrillators.